Hubungan tingkat depresi dengan fungsi kognitif pada lansia - Hasbiah, Isratul; Kholidah, Nurilla; Putri, Audy Oktavioni Tiara (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Aging causes a decline in physical and psychological functions, including depression and cognitive impairment in the elderly. Depression worsens cognitive decline, negatively impacting the quality of life of the elderly. With the increasing number of elderly people in Indonesia, it is important to understand the relationship between depression and cognitive function to improve their care and quality of life. Purpose: To determine the association between the level of depression and cognitive function in elderly residents. Method: This research used an analytical design with a cross-sectional study approach. The sample size consisted of 74 elderly people selected using a purposive sampling technique. Data collection used the Geriatric Depression Scale-15 (GDS-15) questionnaire to assess depression levels and the Montreal Cognitive Assessment (MoCA-INA) questionnaire to assess cognitive function in the elderly. Data analysis used the Spearman rank correlation test with SPSS software. Results: The majority of respondents were female (36 respondents (48.6%), followed by 47 elderly respondents (63.5%), with no education (25 respondents (33.8%), and 49 respondents (66.2%). The Spearman rank correlation test showed a p-value (0.021) ≤ α (0.05), indicating a significant relationship between depression levels and cognitive function in the elderly. Conclusion: There is a significant relationship between the level of depression and cognitive function in the elderly, appropriate intervention efforts to manage depression in the elderly are very necessary to maintain and improve their cognitive function and quality of life. Keywords: Cognitive Function; Depression; Elderly. Pendahuluan: Penuaan menyebabkan penurunan fungsi fisik dan psikologis, termasuk depresi dan gangguan fungsi kognitif pada lansia. Depresi memperburuk penurunan fungsi kognitif, yang berdampak negatif pada kualitas hidup lansia. Dengan meningkatnya jumlah lansia di Indonesia, penting untuk memahami keterkaitan antara depresi dan fungsi kognitif agar dapat meningkatkan penanganan dan kualitas hidup mereka. Tujuan: Untuk mengetahui hubungan antara tingkat depresi dengan fungsi kognitif pada lansia. Metode: Penelitian desain analitik dengan pendekatan cross sectional study. Jumlah sampel penelitian terdiri dari 74 lansia yang diambil dengan teknik purposive sampling. Pengumpulan data mengguanakan menggunakan kuesioner Geriatric Depression Scale-15 (GDS-15) untuk menilai tingkat depresi dan kuesioner Montreal Cognitive Assesment (MoCA-INA) untuk menilai fungsi kognitif lansia. Analisis data mengguanakan uji korelasi Spearman rank dengan software SPSS. Hasil: Responden terbanyak adalah berjenis kelamin perempuan sebanyak 36 responden (48.6%), kelompok lanjut usia yaitu 47 responden (63.5%), riwayat pendidikan tidak sekolah sebanyak 25 responden (33.8%), dan memiliki riwayat penyakit kronis sebanyak 49 responden (66.2%). Berdasarkan hasil uji korelasi spearman rank menunjukkan nilai p (0.021) ≤ α (0.05), artinya adanya hubungan yang signfikan antara tingkat depresi dan fungsi kognitif pada lansia. Simpulan: Adanya hubungan signifikan antara tingkat depresi dan fungsi kognitif pada lansia, upaya intervensi yang tepat untuk mengelola depresi pada lansia sangat diperlukan guna mempertahankan dan meningkatkan fungsi kognitif serta kualitas hidup mereka. Kata Kunci: Depresi; Fungsi Kognitif; Lansia.